Fixation patterns of individuals with and without Autism Spectrum disorder: Do they differ in shared zones and in zebra crossings? - Cowan, G.; Earl, R.; Falkmer, Torbjorn; Girdler, Sonya; Morris, S.; Falkmer, Marita (2018)
© 2018 Elsevier Ltd. Shared zones are a contemporary traffic zone that promotes equality between multiple road users and efficiently utilizes available space, while simultaneously maintaining safety and function. As this is a relatively new traffic zone, it is important to understand how pedestrians navigate a shared zone and any potential challenges this may pose to individuals with impairments. The aim of this study was to utilize eye-tracking technology to determine fixations and fixation duration on traffic relevant objects, non-traffic relevant objects, and eye contact, in 40 individuals with and without Autism Spectrum Disorder (ASD) in a shared zone and a zebra crossing. It was assumed that individuals with ASD would make less eye contact in the shared zone compared to the group of typically developing adults. A total of 3287 fixations across the shared zone and zebra crossing were analysed for areas of interest that were traffic relevant, non-traffic relevant, and eye contact, and for fixation duration. Individuals with ASD did not display any difference in terms of eye contact in the shared zone and the zebra crossing when compared to the controls. All pedestrians were more likely to look at traffic relevant objects at the zebra crossing compared to the shared zone. Individuals with ASD had an overall shorter fixation duration compared to the control group, indicating people with ASD either process information quickly, or they do not process it for long enough, although these findings require further investigation. While shared zones have many benefits for traffic movement and environmental quality, it appeared that pedestrians displayed safer road crossing behaviours at a zebra crossing than in a shared zone, indicating that more education and environmental adaptations are required to make shared zones safe for all pedestrians.